PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PELANGGAN BENGKEL MOBIL PADA CV GALAXY MAJU BERSAMA DI KOTA BEKASI - Muchammad Bukhori (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the effect of service quality and price on customer loyalty at CV Galaxy Maju Bersama car workshop in Bekasi City. The research employed a quantitative approach with 200 respondents, and data analysis was conducted using SPSS version 25. A series of statistical tests were carried out, including data quality tests, classical assumption tests, hypothesis testing, multiple linear regression analysis, and the coefficient of determination. The results of the t-test show that both service quality and price variables have a positive and significant effect on customer loyalty. Furthermore, the F-test results indicate that these two variables simultaneously exert a significant influence on customer loyalty. Based on these findings, it can be concluded that service quality and affordable pricing play a crucial role in building and maintaining customer loyalty, particularly at car workshops located in Bekasi City. These findings emphasize the importance of excellent service strategies and competitive pricing policies in enhancing customer satisfaction and loyalty.